2011
DOI: 10.3402/ijch.v70i2.17813
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and seasonality of falls amongst old people receiving home help services in a municipality in northern Sweden

Abstract: Objectives. Falls among old people is a well-documented phenomenon; however, falls among people living in the community and receiving home help services have been under-researched. The aim of this study was to investigate the incidence, including possible seasonal variation, circumstances and injuries related to falls among community living home help receivers, and to investigate whether fall incidence is associated with the type and amount of home help services received. Study design. Prospective cohort study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 25 publications
0
25
0
2
Order By: Relevance
“…This is less than the 38% of bedroom falls reported in a study conducted in a frail population,34 but higher than a study conducted in a community-dwelling population which found that 20% of falls occurred in the bedroom 18. Nearly 10% of community-dwelling participants were readmitted to hospital following a fall, and the bedroom was the location where the highest number of injurious falls occurred.…”
Section: Discussionmentioning
confidence: 59%
“…This is less than the 38% of bedroom falls reported in a study conducted in a frail population,34 but higher than a study conducted in a community-dwelling population which found that 20% of falls occurred in the bedroom 18. Nearly 10% of community-dwelling participants were readmitted to hospital following a fall, and the bedroom was the location where the highest number of injurious falls occurred.…”
Section: Discussionmentioning
confidence: 59%
“…Approximately one in every three elders (>65 years) living in a community falls. The incidence rate of falls of older adults living in a community varies from 517 to 683 per 1,000 person-years [2], [3]. Elderly falls are an expensive age related public health problem with four decades of research regarding prevention strategies [4].…”
Section: Introductionmentioning
confidence: 99%
“…As well as this, despite collecting data over a similar timeframe, there are more patients in the pre-intervention group than the postintervention group. This is possibly reflective of the time of year the analysis occurs, with a higher rate of trauma occurring in the summer months relative to the winter [18]. There are a number of endpoints that are not assessed as part of our analysis.…”
Section: Discussionmentioning
confidence: 99%